Investigating the influence of titanium particle size and concentration on osteogenic response of human osteoblasts - in vitro study - Soumya Sheela; Waad Kheder; A B Rani Samsudin (Medical Journals Sweden, 2024)
Purpose: The purpose of this study was to investigate the correlation between the size and concentration of titanium particles and the osteogenic response of human osteoblasts (HOB).  Materials and Methods: Different concentrations of titanium dioxide nano- and micro-particles were prepared and their biocompatibility on HOBs was analyzed using XTT assay. The changes in the actin cytoskeletal organization were studied by confocal laser scanning microscopy. The generation of intracellular reactive oxygen species (ROS) by HOBs after exposure to titanium dioxide particles was analyzed using ROS assay. Besides, the osteogenic potential represented by alkaline phosphatase activity, osteoprotegerin, macrophage colony stimulating factor levels, and biomineralization were analyzed. Results: Short-term interaction of titanium dioxide nano- and micro-particles did not induce toxicity to HOBs. However, cells treated with 100 μg/mL titanium dioxide nano- and micro-particles demonstrated higher ROS generation compared to control. Besides, cells treated with 100 µg/mL titanium dioxide nanoparticles showed higher alkaline phosphatase activity, osteoprotegerin, macrophage colony stimulating factor levels and biomineralization compared to titanium dioxide microparticles.  Conclusion: Collectively, the study found titanium dioxide nanoparticles to be more biocompatible than microparticles providing an insight into the capability of nanostructures in supporting osteoblast differentiation and its plausibility in biomedical applications.